2018
DOI: 10.1002/aic.16158
|View full text |Cite
|
Sign up to set email alerts
|

Controllable fabrication and catalytic performance of nanosheet HZSM‐5 films by vertical secondary growth

Abstract: Significance Nanosheet HZSM-5 film vertically grown on the substrate with the tailorable macro-and meso-pores between the layers of nanosheets is hydrothermally synthesized by seed-assisted secondary growth method. The asprepared nanosheet HZSM-5 film exhibits reaction rate enhancement up to 312% in catalytic cracking of n-dodecane as well as twice light olefins selectivity, ascribed to the better mass transfer of reactants in the hierarchical porous structure and the ultra-thin b-axis pores of nanosheets. a S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…The specific value of L / B decreases in the order of Z‐130 > Z‐200 > Z‐300 > Z‐60 > Z‐18, and the total Brønsted acid sites reduce with the decrease of Al content. Since the diameter of DTBPy (1.05 nm) is much larger than the size of micropores in HZSM‐5 (0.53 × 0.56 nm), it can be used to study the B acid sites on the external surface . As exhibited in Figure b, the peak at around 1,610 cm −1 is attributed to DTBPy bonded to surface B acid sites.…”
Section: Resultsmentioning
confidence: 99%
“…The specific value of L / B decreases in the order of Z‐130 > Z‐200 > Z‐300 > Z‐60 > Z‐18, and the total Brønsted acid sites reduce with the decrease of Al content. Since the diameter of DTBPy (1.05 nm) is much larger than the size of micropores in HZSM‐5 (0.53 × 0.56 nm), it can be used to study the B acid sites on the external surface . As exhibited in Figure b, the peak at around 1,610 cm −1 is attributed to DTBPy bonded to surface B acid sites.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the morphology of MFI nanosheets can be changed from a disordered assembly to an ordered multilamellar structure when increasing the hydrothermal aging time [12]. To control nanosheet structures, there are several types of surfactants, in particular, quaternary ammonium surfactants, as well as other templates or seeds that have been developed to synthesize various hierarchical zeolite nanosheets with different morphologies [13][14][15]. For example, tetrapropylammonium hydroxide (TPAOH) was used together with C 22−6−6 as a dual-template to control hierarchical structures [13].…”
Section: Synthesis Of Hierarchical Zeolite Nanosheetsmentioning
confidence: 99%
“…When increasing the amount of TPAOH, the morphology of the MFI nanosheet changes from intertwined particles to house-of-cards-structures. In addition, nanosheet HZSM-5 films deposited on the support and the hierarchical MFI nanosponge were successfully synthesized using C 22-6-6 in seed-assisted synthesis methods [14,15]. Their hierarchical structures exhibit the remarkably improved activity attributing to the enhanced accessibility and diffusion of bulky molecules into the zeolite framework.…”
Section: Synthesis Of Hierarchical Zeolite Nanosheetsmentioning
confidence: 99%
“…It exhibited a high catalytic stability on n-hexane cracking since it was less sensitive to the deactivation by coke [14]. The MFI zeolite with ultrathin nanosheet morphology showed a higher BET surface area and pore volume, which facilitated the transport of reactants, resulting in higher activity comparing with the conventional ZSM-5 zeolite [15][16][17]. The ZSM-5 zeolite with a hollow fiber morphology facilitated the cracking of n-butane and the generation of light alkenes due to the hierarchical porosity [18].…”
Section: Introductionmentioning
confidence: 99%